2018
DOI: 10.3389/fcvm.2018.00070
|View full text |Cite|
|
Sign up to set email alerts
|

The Regulation of Insulin-Stimulated Cardiac Glucose Transport via Protein Acetylation

Abstract: Cellular catabolism is the cell capacity to generate energy from various substrates to sustain its function. To optimize this energy production, cells are able to switch between various metabolic pathways in accordance to substrate availability via a modulation of several regulatory enzymes. This metabolic flexibility is essential for the healthy heart, an organ requiring large quantities of ATP to sustain its contractile function. In type 2 diabetes, excess of non-glucidic nutrients such as fatty acids, branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…19 In line, we recently showed that increased protein acetylation by metabolic over-fuelling dramatically reduced both insulin-and AMPK-mediated glucose uptake in cardiomyocytes, presuming the importance of reducing protein acetylation for promoting glucose metabolism during IRI. 110,111 Overall, while promoting deacetylation, for example by targeting SIRT1 activation, is an attractive avenue for cardioprotection, considerable effort is required for the development of specific drugs to achieve this end.…”
Section: Lysine Acetylation Of Cardiac Proteinsmentioning
confidence: 99%
“…19 In line, we recently showed that increased protein acetylation by metabolic over-fuelling dramatically reduced both insulin-and AMPK-mediated glucose uptake in cardiomyocytes, presuming the importance of reducing protein acetylation for promoting glucose metabolism during IRI. 110,111 Overall, while promoting deacetylation, for example by targeting SIRT1 activation, is an attractive avenue for cardioprotection, considerable effort is required for the development of specific drugs to achieve this end.…”
Section: Lysine Acetylation Of Cardiac Proteinsmentioning
confidence: 99%
“…Acetylation is a post-translational modification that can modify the activity glucose and fatty acid metabolism regulatory enzymes [47, 48]. Overall protein acetylation in the MI heart was not changed compared to sham group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increased fatty acid oxidation leads to increased levels of acetyl-CoA and of protein acetylation. On its turn, protein acetylation inhibits insulin signaling at multiple levels as well as insulin-stimulated GLUT4 translocation via unknown mechanisms [26]. The fatty acid metabolites are mostly made up of triacylglycerols stored in lipid droplets.…”
Section: The Heart During Lipid Overloadmentioning
confidence: 99%